Isolation and Characterization of Human Lung Lymphatic Endothelial Cells. (7th June 2015) - Lorusso, Bruno; Falco, Angela; Madeddu, Denise; Frati, Caterina; Cavalli, Stefano; Graiani, Gallia; Gervasi, Andrea; Rinaldi, Laura; Lagrasta, Costanza; Maselli, Davide; Gnetti, Letizia; Silini, Enrico M.; et al.
Abstract : Characterization of lymphatic endothelial cells from the respiratory system may be crucial to investigate the role of the lymphatic system in the normal and diseased lung. We describe a simple and inexpensive method to harvest, isolate, and expand lymphatic endothelial cells from the human lung (HL-LECs). Fifty-five samples of healthy lung selected from patients undergoing lobectomy were studied. A two-step purification tool, based on paramagnetic sorting with monoclonal antibodies to CD31 and Podoplanin, was employed to select a pure population of HL-LECs. The purity of HL-LECs was assessed by morphologic criteria, immunocytochemistry, flow cytometry, and functional assays. Interestingly, these cells retain in vitro several receptor tyrosine kinases (RTKs) implicated in cell survival and proliferation. HL-LECs represent a clinically relevant cellular substrate to study lymphatic biology, lymphoangiogenesis, interaction with microbial agents, wound healing, and anticancer therapy.